Chemical constituents and cytotoxic activities of the extracts of Melilotus indicus - Ahmed, Sayed Abdel Kader; Al-Refai, Mahmoud (European Journal of Chemistry, 2014)
The phytochemical investigation of the ethanolic extract of the aerial parts of Melilotus indicus resulted in the isolation of eight known flavonoids, namely; catechin (1), epicatechin (2), taxifolin (3), quercetin (4), quercetin 3-O-β-D-glucopyranoside (5), and quercetin 3-O-α-L-rhamnopyranoside (6), isorhamnetin 3-O-β-D-glucopyranoside (7) and isorhamnetin 3-O-β-D-rutinoside (8). These compounds have never been isolated from this species. The cytotoxic activities of the extracts of Melilotus indicus was evaluated by MTT assay against six cancer cell lines using doxorubicin as standard drug. The chloroform extract was the most potent cytotoxic agent against HepG-2cells with an IC50: 9.21 µg/mL.